2018
DOI: 10.1093/brain/awy105
|View full text |Cite
|
Sign up to set email alerts
|

JAK inhibitor improves type I interferon induced damage: proof of concept in dermatomyositis

Abstract: Dermatomyositis is an acquired auto-immune disease characterized by skin lesions and muscle-specific pathological features such as perifascicular muscle fibre atrophy and vasculopathy. Dermatomyositis patients display an upregulation of type I interferon-inducible genes in muscle fibres, endothelial cells, skin and peripheral blood. However, the effect of type I interferon on muscle tissue has not yet been determined. Our aim was to study the pathogenicity of type I interferon in vitro and to evaluate the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(159 citation statements)
references
References 70 publications
7
143
0
5
Order By: Relevance
“…We showed MxA expression for the first time in endothelial cells, smooth muscle cells and pericytes of the diseased arterioles, in addition to capillaries described in previous studies [22]. In-vitro studies have confirmed that the presence of type I interferon led to a reduction in the number of meshes and junctions of microvascular endothelial cells with significant upregulation of MxA [23]. In addition, extensive expression of MxA was seen in smooth muscle cells of diseased perimysial arterioles and endomysial neovessels with thick muscular coats and widely opened lumens, indicating the involvement of type I interferon signaling in smooth muscle cells.…”
Section: Discussionsupporting
confidence: 81%
“…We showed MxA expression for the first time in endothelial cells, smooth muscle cells and pericytes of the diseased arterioles, in addition to capillaries described in previous studies [22]. In-vitro studies have confirmed that the presence of type I interferon led to a reduction in the number of meshes and junctions of microvascular endothelial cells with significant upregulation of MxA [23]. In addition, extensive expression of MxA was seen in smooth muscle cells of diseased perimysial arterioles and endomysial neovessels with thick muscular coats and widely opened lumens, indicating the involvement of type I interferon signaling in smooth muscle cells.…”
Section: Discussionsupporting
confidence: 81%
“…Ruxolitinib (Jakafi or Jakavi) is a licensed, orally administered JAK1/JAK2 inhibitor used to treat neoplastic diseases, particularly myelofibrosis (Harrison et al, 2012;Verstovsek et al, 2012). Recently, this drug was used with some success to treat children with a type I interferonopathy (Fré mond et al, 2016) and dermatomyositis patients with type I IFN-mediated disruption of vascular endothelial networks (Ladislau et al, 2018). Therefore, we repeated the above therapeutic protocol but replaced the anti-IFNaR1 mAb with ruxolitinib.…”
Section: Type I Ifns Act On Dcs To Suppress Development Of Antigen-spmentioning
confidence: 99%
“…For this reason, ASS was suggested to be a unique myositis subtype at the European Neuromuscular Centre International Workshop [9]. Importantly, increasing number of reports suggest the therapeutic efficacy of JAK inhibitors such as tofacitinib and ruxolitinib in refractory DM [10,11]. JAK plays a key role in the expression of type 1 interferon-inducible genes, including MxA, in the target organs, by phosphorylating the transcriptional factors for interferon-inducible genes, STAT1 and STAT2.…”
mentioning
confidence: 99%